Variability in Total Cholesterol Concentration Is Associated With the Risk of Dementia: A Nationwide Population-Based Cohort Study - Chung, Hye Soo; Lee, Ji Sung; Kim, Jung A.; Roh, Eun; Lee, You Bin; Hong, So Hyeon; Kim, Nam Hoon; Yoo, Hye Jin; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Baik, Sei Hyun; et al. (Frontiers in Neurology, 2019)
Introduction: Although total cholesterol (TC) variability suggested for a risk factor for cardiovascular and cerebrovascular disease, there was no previous study to evaluate the association between TC variability and the development of dementia. Methods: Using the Korean National Health Insurance Service–Health Screening Cohort (NHIS-HEALS), the main outcomes were newly diagnosed all-cause dementia, Alzheimer’s disease (AD), or vascular dementia (VaD) between January 1, 2008, and December 31, 2015. Visit-to-visit TC variability was measured as variability independent of the mean (TC-VIM), coefficient variance (TC-CV), and standard deviation (TC-SD). Results: In a total of 131,965 Koreans, there were 3,722 all-cause dementia (2.82%), 2,776 AD (2.10%), and 488 VaD (0.37%) during the median follow-up of 8.4 years. Kaplan-Meier curves showed increased cumulative incidences for all in the highest quartiles of TC variability group compared to the others. Regression using Fine and Gray hazards model showed a steadily increasing risk of all-cause dementia with higher quartiles of TC variability. After adjusting for confounders including mean TC level and comparing the highest and lowest TC-VIM quartiles, the hazard ratios (HRs) for all-cause dementia and AD were 1.15 (95% confidence interval [CI] = 1.05 - 1.27; P = 0.003) and 1.12(95% CI = 1.00 - 1.25; P = 0.040), respectively. The incidence of VaD was not significantly higher in the higher-quartile groups compared to that in the lowest-quartile group in TC-VIM variability (HR 1.22; 95% CI = 0.95 - 1.59; P = 0.122). These associations were consistent with TC variability defined by TC-CV or TC-SD. Conclusions: For the first time, we have demonstrated that a higher visit-to-visit variability in TC independent of mean TC was associated with an increased risk of all-cause dementia and AD in the general population.